Pengembangan Media Lectora Inspire 18 Berbasis PBL untuk Meningkatkan Minat dan Hasil Belajar Pendidikan Pancasila Siswa Kelas IV Sekolah Dasar - Sihombing, Ester Lydia; Aeni, Kurotul (Universitas Muhammadiyah Magelang, 2025)
Pancasila Education plays a crucial role in shaping the national character and civic responsibility of elementary school students. However, the use of conventional teaching methods and the lack of engaging instructional media have resulted in low student interest and achievement, particularly in Grade IV. This study aims to develop an interactive learning media using Lectora Inspire 18 combined with the Problem-Based Learning (PBL) model to improve students’ interest and learning outcomes in Pancasila Education. The research employed a Research and Development (R&D) method, following a simplified Borg & Gall model as modified by Sugiyono, and applied a Pre-Experimental One-Group Pretest-Posttest Design. The participants included fourth-grade students, classroom teachers, as well as media and content experts. Data were collected through questionnaires, observations, interviews, and pretest-posttest assessments. Validation results indicated that the media was highly feasible, with expert ratings of 92.39% for content and 88.23% for media. The effectiveness test showed a significant improvement in students’ interest, from 46.11% to 91.85%, and in learning outcomes, from an average score of 53.52 to 88.52. Statistical analysis using a paired sample t-test confirmed a significant difference (p < 0.05), and the N-Gain scores indicated a high level of improvement in both learning interest (84.61%) and outcomes (74.91%). These results demonstrate that the integration of Lectora Inspire 18 with the PBL model is not only feasible but also effective in enhancing student engagement and academic performance in Pancasila Education at the elementary school level.